Potensi Mahasiswa Dalam Mengimplementasikan Minat Pada Proses Pembelajaran - Razali Tahib (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2016)
That somebody enthusiasm to a mirror object from its behavior, and that enthusiasm is background by somebody attention to certain enthusiasm object, that is attention, feel to like to know high, and requirement will determine in select to something popular object it. Hence for that, somebody enthusiasm of depend on attention, feel to like to know the, requirement and selection to chosen the popular activity it. Enthusiasm also represent basis for reach for the efficacy for somebody. If student somebody hanker to a eye learn, hence entire/all attention, feel to like to know, and student requirement to a eye learn of excelsior, so that excelsior will also result of learning which is reached for student from a eye learn followed.